2008
DOI: 10.1016/j.expneurol.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill training promotes axon regeneration in injured peripheral nerves

Abstract: Physical activity after spinal cord injury promotes improvements in motor function, but its effects following peripheral nerve injury are less clear. Although axons in peripheral nerves are known to regenerate better than those in the CNS, methods of accelerating regeneration are needed due to the slow overall rate of growth. Therefore we studied the effect of two weeks of treadmill locomotion on the growth of regenerating axons in peripheral nerves following injury. The common fibular nerves of thy-1-YFP-H mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(177 citation statements)
references
References 28 publications
5
153
0
5
Order By: Relevance
“…With regard to LT, our results show that it did not have a beneficial effect on soleus and TA muscle performance after NT. Therefore, our findings suggest that the possible increased nerve regeneration induced by LT or electrostimulation observed by histological analysis 4,8,9 has no major impact on muscle weakness and functional innervation. Discrepancies between nerve histology, motor function, and electrophysiology measures have been reported to occur during muscle reinnervation.…”
Section: Lt Had No Effect When Fully Functional Innervationmentioning
confidence: 63%
See 2 more Smart Citations
“…With regard to LT, our results show that it did not have a beneficial effect on soleus and TA muscle performance after NT. Therefore, our findings suggest that the possible increased nerve regeneration induced by LT or electrostimulation observed by histological analysis 4,8,9 has no major impact on muscle weakness and functional innervation. Discrepancies between nerve histology, motor function, and electrophysiology measures have been reported to occur during muscle reinnervation.…”
Section: Lt Had No Effect When Fully Functional Innervationmentioning
confidence: 63%
“…Increased neuromuscular activity via physical exercise, such as locomotor training (LT) and electrostimulation, have been shown to improve nerve regeneration and muscle reinnervation, as assessed using histological measures [4][5][6][7][8][9] and analysis of coordinated and complex motor functions, namely toe-spreading reflex and locomotion. 6,10 Together these earlier studies suggested that increased neuromuscular activity may improve the full recovery of muscle performance after nerve injury, such as maximal force production.…”
Section: Muscle Nerve 45: 567-577 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Several experiments involving denervated animals 18 have described exercise as the factor that provides the most budding and extension of the axons, 12 the greatest increase in the number of myelinated fibers 13,14 and the best improvement in functional recovery for the injured member 15 . The results from this study are similar to those found in the literature regarding evaluating functional recovery, due to the fact that the groups that performed exercise showed better results compared to groups who did not go through the swimming protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown beneficial results by using exercise, namely through greater budding and extension of the axons 12 , increased number of myelinated nerve fibers, 13,14 and improved functional recovery of the injured member [15][16][17] . There have been extensive discussions in the scientific community 18 regarding recommendations as per the type of exercise as well as its duration and intensity.…”
Section: Introductionmentioning
confidence: 99%